Preparation method of portable electrochemical sensor for specifically detecting tyrosine
Through a portable electrochemical sensor, a specific electrochemical induction probe composed of modified two-dimensional layered carbon/nitride, gold nanoparticles and molecularly imprinted gel is used to achieve high selectivity, rapid and accurate detection of tyrosine, solving the complex and interference problems in the prior art, and achieving high sensitivity and stability.
Patent Information
- Application Number
- CN202411608064.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve high selectivity, rapid and accurate detection of tyrosine, and the traditional methods require professional operation and are easily interfered with amino acids with similar structures, resulting in misdiagnosis and misinterpretation of treatment.
The portable electrochemical sensor is used to detect it using flexible screen-printed electrodes and specific electrochemical induction probes. The probe consists of modified two-dimensional layered carbon/nitrides, gold nanoparticles and molecularly imprinted gels to achieve specific recognition of tyrosine through electrostatic interactions and hydrogen bond interactions.
High selectivity, rapid and accurate detection of tyrosine is achieved, and structurally similar amino acid interference is avoided, operation is simplified, dependence on professionals is reduced, and the sensor has high sensitivity and stability.
Smart Images

Figure HDA0005130167890000011 
Figure HDA0005130167890000012 
Figure HDA0005130167890000021
Abstract
Description
Technical Field
[0001] The invention relates to the fields of nano material synthesis and testing technology, and in particular to a method for preparing a portable electrochemical sensor for specifically detecting tyrosine. Background Art
[0002] The medical community has proven that amino acids are clinically biomarkers for some serious diseases, and their quantitative analysis is gaining more and more attention. For example, tyrosine, which is converted from phenylalanine, has an endogenous level that is related to melanin synthesis, and the content of melanin is directly related to albinism. Therefore, the level of tyrosine in the human body is of great significance for the early warning of albinism. Therefore, clinically, real-time detection of tyrosine is crucial for indicating the evaluation of the functional status of the human body. However, for the quantitative detection of such amino acid small molecules, the academic community has found two arduous tasks under continuous research efforts. One is that it is increasingly difficult to develop real-time diagnostic technology and corresponding detection equipment. Another inevitable challenge is that some structurally similar amino acids in the human body, such as phenylalanine and tryptophan, can seriously interfere with the accurate quantification of tyrosine, which can lead to misdiagnosis of albinism and misinterpretation of the treatment level of albinism. Therefore, the rapid and accurate detection of tyrosine with high selectivity is a great challenge.
[0003] To overcome these obstacles, point-of-care (POC) detection equipment can meet the real-time monitoring requirements of target amino acid molecules, which has the advantages of convenience and low cost. In addition, molecular imprinting technology (MIT) is an effective tool for achieving selective recognition of target molecules. Its inspiration, molecularly imprinted polymers (MIPs), is inspired by the specific binding relationship between antigens and antibodies. It is worth noting that the reasonable design of MIPs structure is the key to improving the recognition accuracy of target molecules, and it is also the difficulty.
[0004] In addition, the academic community has already used chromatography, mass spectrometry, enzyme-linked immunosorbent assay and other detection methods for the quantitative determination of tyrosine. Although some methods have achieved specific recognition of tyrosine, these traditional methods still suffer from complex test operations and difficulties in operating in large instruments, requiring professional testers to be strictly trained before they can be carried out.
[0005] Based on this background, there is an urgent need to develop an efficient and convenient diagnostic tool for real-time detection of tyrosine in human body fluids. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The inventors found that the existing literature reports on the use of electrochemical methods to detect tyrosine can neither guarantee the false positive signals of other interfering molecules in the detection process, nor require the test operation to be performed on a relatively bulky electrochemical workstation. Therefore, ensuring the detection specificity and sensitivity of the probe, as well as developing a handheld portable electrochemical sensor, are the research difficulties of this work. To this end, one purpose of the present invention is to provide an efficient and convenient diagnostic tool for real-time detection of tyrosine in human body fluids.
[0007] In one aspect of the present invention, the present invention proposes a portable electrochemical sensor for the specific detection of tyrosine. According to an embodiment of the present invention, the portable electrochemical sensor for the specific detection of tyrosine comprises: a flexible screen-printed electrode, the substrate of the flexible screen-printed electrode is a polyethylene terephthalate film, and the flexible screen-printed electrode is printed with graphite ink and silver paste ink; an electrochemical sensing probe, the electrochemical sensing probe is located on the surface of the flexible screen-printed electrode, and the electrochemical sensing probe is composed of a ternary composite material, and the ternary composite material includes a two-dimensional layered carbon / nitride, gold nanoparticles and molecular imprinting gel. According to an embodiment of the present invention, the present invention proposes a portable electrochemical sensor for the detection of tyrosine with strong specificity, high sensitivity and good stability, and its structure includes a flexible screen-printed electrode (SPE) and a specific electrochemical sensing probe modified on the surface of its working electrode; the substrate of the specific electrochemical sensing probe is a two-dimensional layered modified MXene and gold (Au) nanoparticles, and the two are combined by electrostatic action; the outside is a specific molecular imprinting gel (MIG), which completely wraps the modified MXene / Au. The design concept and principle of the present invention is to use modified MXene and Au nanoparticles with high electrochemical activity as the probe substrate, and MIG similar to artificial antibodies as the specific recognition cavity. It has high applicability and stable properties, and can achieve specific recognition and detection of tyrosine. The technical difficulty overcome by the present invention lies in the design and preparation of specific electrochemical sensing probes, in which the original MXene has poor stability and limited electrochemical activity. After secondary modification, not only the stability of the material itself is improved, but also its electrochemical performance is greatly improved; MIG specifically captures free tyrosine molecules through hydrogen bond interactions, and then performs electrochemical redox reactions. In addition, biomass chitosan is also used in the encapsulation of the modified MXene / Au / MIG of the specific electrochemical sensing probe, thereby avoiding the toxicity of the traditional adhesive perfluorosulfonic acid resin (Nafion), which is suitable for human body fluid detection.
[0008] According to an embodiment of the present invention, the portable electrochemical sensor for specific detection of tyrosine may further include the following additional technical features:
[0009] According to an embodiment of the present invention, the two-dimensional layered carbon / nitride and the gold nanoparticles are connected together through electrostatic interaction.
[0010] In another aspect of the present invention, the present invention also proposes a method for preparing a portable electrochemical sensor for specific detection of tyrosine. According to an embodiment of the present invention, the method comprises:
[0011] S1: dispersing the MAX phase in an acidic solution, and removing the aluminum layer in the MAX phase through a first etching treatment to obtain an original two-dimensional layered carbon / nitride, wherein the MAX phase is a non-van der Waals layered compound;
[0012] S2: dispersing the original two-dimensional layered carbon / nitride in an alkaline solution, and subjecting the original two-dimensional layered carbon / nitride to a second etching treatment to obtain a modified two-dimensional layered carbon / nitride;
[0013] S3: dispersing the modified two-dimensional layered carbon / nitride in a chloroauric acid solution and mixing with a reducing agent to obtain a modified two-dimensional layered carbon / nitride / gold;
[0014] S4: dispersing the modified two-dimensional layered carbon / nitride / gold in acetonitrile, and polymerizing with a template molecule, a functional monomer, a cross-linking agent, and an initiator to obtain a molecularly imprinted gel;
[0015] S5: washing, centrifuging and drying the molecularly imprinted gel to obtain a specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecularly imprinted gel;
[0016] S6: The specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is fixed to the surface of a flexible screen-printed electrode to obtain a portable electrochemical sensor for specific detection of tyrosine.
[0017] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0018] According to an embodiment of the present invention, the chemical composition of the MAX phase is one or both of Ti3AlC2 and Ti2AlC. These two MAX phases are the most common and widely used in the academic community, with stable properties and controllable costs.
[0019] According to an embodiment of the present invention, the mass concentration of the MAX phase in the first etching process is 0.04-0.06 g mL -1 .
[0020] According to an embodiment of the present invention, the acidic solution is one or more of a hydrofluoric acid aqueous solution, hydrochloric acid or a lithium fluoride mixed solution.
[0021] According to an embodiment of the present invention, the mass fraction of the acid solution in the first etching process is 30%-50%.
[0022] According to an embodiment of the present invention, the temperature of the first etching process is 30-50°C.
[0023] According to an embodiment of the present invention, the time of the first etching process is 24-48 hours.
[0024] According to an embodiment of the present invention, the solute of the alkaline solution is one or more of potassium hydroxide, sodium hydroxide, and p-phenylenediamine.
[0025] According to an embodiment of the present invention, the reaction molar concentration of the alkaline solution in the second etching process is 1-3M.
[0026] According to an embodiment of the present invention, the reaction time of the second etching process is 12-24 hours.
[0027] According to an embodiment of the present invention, the mass concentration of the modified two-dimensional layered carbon / nitride in the mixing process is 1-5 mg mL -1 .
[0028] According to an embodiment of the present invention, the mass concentration of the chloroauric acid solution in the mixing process is 1-2 wt.%.
[0029] According to an embodiment of the present invention, the reducing agent is one or more of citric acid, hydrated citric acid or sodium citrate.
[0030] According to an embodiment of the present invention, the mass concentration of the reducing agent in the mixing process is 1-2 wt.%.
[0031] According to an embodiment of the present invention, the mixing treatment time is 1-4 hours.
[0032] According to an embodiment of the present invention, the mass concentration of acetonitrile is 0.5-2 mg mL -1 .
[0033] According to an embodiment of the present invention, the template molecule is tyrosine.
[0034] According to an embodiment of the present invention, the molar concentration of the template molecule in acetonitrile is 0.01-0.02M.
[0035] According to an embodiment of the present invention, the functional monomer is one or more of acrylamide, acrylic acid or 4-vinylpyridine.
[0036] According to an embodiment of the present invention, the molar concentration of the functional monomer in acetonitrile is 0.04-0.08M.
[0037] According to an embodiment of the present invention, the cross-linking agent is one or both of N,N-methylenebisacrylamide and ethylene glycol dimethacrylate.
[0038] According to an embodiment of the present invention, the molar concentration of the cross-linking agent in acetonitrile is 0.05-0.2M.
[0039] According to an embodiment of the present invention, the initiator is one or both of dibenzoyl peroxide and azobisisobutyronitrile.
[0040] According to an embodiment of the present invention, the mass concentration of the initiator in acetonitrile is 0.2-1 mg mL -1 .
[0041] According to an embodiment of the present invention, the polymerization reaction is carried out in an oxygen-free environment.
[0042] According to an embodiment of the present invention, the polymerization reaction temperature is 55-65°C.
[0043] According to an embodiment of the present invention, the polymerization reaction time is 8-24h.
[0044] According to an embodiment of the present invention, the molar ratio of the template molecule, the functional monomer, and the cross-linking agent is 1:4:10.
[0045] According to an embodiment of the present invention, the eluent in the washing treatment is one or more of methanol, ethanol, formic acid or acetic acid.
[0046] According to an embodiment of the present invention, the number of elutions in the washing process is 3-5 times.
[0047] According to an embodiment of the present invention, the drying process is performed by freeze drying.
[0048] According to an embodiment of the present invention, the specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is fixed to the surface of the flexible screen-printed electrode in the following manner:
[0049] A1: Grind the biomass chitosan finely and then dissolve it in an organic acid solution to obtain a sensing probe adhesive;
[0050] A2: Use graphite ink and silver paste ink to print flexible screen-printed electrodes according to the pre-made screen, and dry completely;
[0051] A3: The specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is dispersed in the adhesive to obtain a uniform suspension, the suspension is pipetted and dripped onto the working electrode surface of the flexible screen-printed electrode, and after drying, a portable electrochemical sensor for specific detection of tyrosine is obtained.
[0052] According to an embodiment of the present invention, the adhesive is chitosan acetic acid solution or chitosan formic acid solution.
[0053] According to an embodiment of the present invention, the mass concentration of the adhesive is 1-5 mg mL -1 .
[0054] According to an embodiment of the present invention, the concentration of the modified two-dimensional layered carbon / nitride / gold / molecularly imprinted gel in the adhesive is 1-5 mg mL -1 .
[0055] According to an embodiment of the present invention, the amount of the suspension is 5-10 μL.
[0056] According to an embodiment of the present invention, the dry environment is a vacuum environment.
[0057] According to an embodiment of the present invention, the drying temperature is 30-40°C.
[0058] In another aspect of the present invention, the present invention also proposes a portable electrochemical sensor for specific detection of tyrosine. According to an embodiment of the present invention, the structure of the portable electrochemical sensor for specific detection of tyrosine includes a flexible screen-printed electrode (SPE) and a specific electrochemical sensing probe modified on its surface; the substrate of the SPE is a polyethylene terephthalate (PET) film, and the electrode is printed with graphite ink and silver paste ink; the specific electrochemical sensing probe is a ternary composite material of modified two-dimensional layered carbon / nitride (MXene), gold (Au) nanoparticles and molecularly imprinted gel (MIG), wherein the modified MXene and Au nanoparticles are connected by electrostatic interaction to obtain modified MXene / Au, and MIG is in situ polymerized and grown on the modified MXene / Au to obtain modified MXene / Au / MIG.
[0059] In another aspect of the present invention, the present invention also provides a method for preparing a portable electrochemical sensor for specific detection of tyrosine as described above. According to an embodiment of the present invention, the method comprises the following steps:
[0060] (1) Preparation of specific electrochemical sensing probes:
[0061] The MAX phase (a non-van der Waals type layered compound) is dispersed in an acidic solution, the aluminum layer in the MAX phase is removed after a long period of etching, and the original MXene is obtained by washing, centrifugation and drying;
[0062] The original MXene is dispersed in an alkaline solution, the carbon layer and the residual aluminum layer are secondary etched for a long time, and the modified MXene is obtained by washing, centrifugation and drying;
[0063] The modified MXene is dispersed in a chloroauric acid solution, an appropriate amount of a citric acid reducing agent is added, and the modified MXene / Au is obtained by washing, centrifuging and drying.
[0064] The modified MXene / Au was dispersed in acetonitrile, and the template molecule tyrosine, the functional monomer, and the cross-linking agent were added in a molar ratio of 1:4:10, and then an appropriate amount of thermal initiator was added. After removing oxygen, polymerization reaction was carried out, and the template molecule tyrosine was cleaned to obtain MIG, which was washed, centrifuged and dried to obtain the specific electrochemical sensing probe modified MXene / Au / MIG;
[0065] (2) Preparation of a portable electrochemical sensor for specific detection of tyrosine:
[0066] The biomass chitosan is finely ground and then dissolved in an organic acid solution to obtain a sensing probe adhesive;
[0067] Use graphite (carbon) ink and silver paste ink to print SPE according to the pre-made screen and dry it completely;
[0068] The specific electrochemical sensing probe modified MXene / Au / MIG is dispersed in the above-mentioned adhesive to obtain a uniform suspension, and an appropriate amount of the suspension is added dropwise to the working electrode surface of the SPE, and dried at room temperature to obtain a portable electrochemical sensor for specific detection of tyrosine.
[0069] According to an embodiment of the present invention, the above method may further include at least one of the following additional technical features:
[0070] According to an embodiment of the present invention, in step (1), the chemical composition of the MAX phase is one or more of Ti3AlC2 and Ti2AlC, and the final reaction mass concentration is 0.04-0.06 g mL -1 .
[0071] According to an embodiment of the present invention, in step (1), the acidic solution is one or more of a hydrofluoric acid aqueous solution, a hydrochloric acid & lithium fluoride mixed solution, and the final reaction mass fraction of the solution is 30%-50%.
[0072] According to an embodiment of the present invention, in the step (1), the preparation reaction temperature of the original MXene is 30-50° C., the reaction time is 24-48 h, and the drying method is freeze-drying.
[0073] According to an embodiment of the present invention, in step (1), the solute of the alkaline solution is one or more of potassium hydroxide, sodium hydroxide, and p-phenylenediamine, and the final reaction molar concentration of the alkaline solution is 1-3M.
[0074] According to an embodiment of the present invention, in the step (1), the preparation reaction time of the modified MXene is 12-24 hours, and the drying method is freeze-drying.
[0075] According to an embodiment of the present invention, in step (1), the final reaction mass concentration of the modified MXene is 1-5 mg / mL -1 ; The mass concentration of chloroauric acid solution is 1-2wt.%; the reducing agent is one or more of citric acid, hydrated citric acid, and sodium citrate, with a mass concentration of 1-2wt.%, and the reduction time is 1-4h.
[0076] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the substrate is prefabricated modified MXene / Au, and the mass concentration in the solvent acetonitrile is 0.5-2 mg mL -1 .
[0077] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the template molecule is tyrosine, and the molar concentration of tyrosine in the solvent acetonitrile is 0.01-0.02M.
[0078] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the functional monomer is one or more of acrylamide (AM), acrylic acid (AA), and 4-vinylpyridine (4VP), and the molar concentration in the solvent acetonitrile is 0.04-0.08M.
[0079] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the cross-linking agent is one or more of N,N-methylenebisacrylamide (MBA) or ethylene glycol dimethacrylate (EGDMA), and the molar concentration in the solvent acetonitrile is 0.05-0.2M.
[0080] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the initiator is one or more of dibenzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN), and the mass concentration in the solvent acetonitrile is 0.2-1 mg mL -1 .
[0081] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the polymerization environment is an oxygen-free environment, the polymerization reaction temperature is 55-65° C., and the polymerization reaction time is 8-24 h.
[0082] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the eluent is one or more of methanol, ethanol, formic acid, and acetic acid, the number of elutions is 3-5 times, and the drying method is freeze-drying.
[0083] According to an embodiment of the present invention, in step (2), the adhesive is chitosan acetic acid solution or chitosan formic acid solution, wherein the mass concentration of chitosan is 1-5 mg mL -1 The concentration of probe-modified MXene / Au / MIG in the adhesive was 1-5 mg mL -1 .
[0084] According to an embodiment of the present invention, in step (2), the working electrode of SPE is printed with graphite (carbon) ink, the reference electrode is printed with silver paste ink, and the counter electrode is printed with graphite (carbon) ink.
[0085] According to an embodiment of the present invention, in the step (2), the amount of the sensing probe suspension is 5-10 μL, the drying environment is vacuum, and the drying temperature is 30-40° C.
[0086] According to an embodiment of the present invention, in step (1), the chemical composition of the MAX phase is Ti3AlC2 or Ti2AlC; these two MAX phases are the most common and widely used in academia, with stable properties and controllable costs.
[0087] According to an embodiment of the present invention, in step (1), the acidic solution is a hydrofluoric acid solution or a mixed solution of lithium fluoride and hydrochloric acid; wherein the concentration of the hydrofluoric acid solution is generally 40%; in the lithium fluoride and hydrochloric acid system, the hydrochloric acid concentration is 9M, and the mass concentration of lithium fluoride is 0.05gmL -1 When the concentration is higher or lower than the above range, the etching effect on the MAX phase is poor, the original MXene with an "accordion" morphology cannot be obtained, and it will cause certain secondary pollution.
[0088] According to an embodiment of the present invention, in the step (1), the etching reaction temperature of the MAX phase is 30-50°C, the reaction time is 24-48h, and the drying method is freeze-drying. If the reaction temperature is lower than the above range, the etching effect is poor and a two-dimensional "accordion" structure cannot be formed; if the temperature is higher than the above range, the reaction is violent, which is dangerous and has high energy consumption; if the reaction time is lower than the above range, the etching effect is poor and a clear lamellar structure cannot be formed; if the reaction time is higher than the above range, the energy consumption is high.
[0089] According to an embodiment of the present invention, in the step (1), the molecule providing alkalinity in the solution is sodium hydroxide, potassium hydroxide or p-phenylenediamine, the final reaction molar concentration of the alkaline solution is 1-3M, the reaction time is 12-24h, and the drying method is freeze-drying. The molar concentration of the alkaline solution directly affects the use effect of the modified MXene. If it is lower than the above concentration range, the modification effect is poor, the hydroxyl group replaces the fluorine group less, and the electrochemical activity is limited. If it is higher than the above concentration range, the carbon layer of the MXene will be further etched to produce a fibrous structure, which affects the use; if the reaction time is lower than the above range, the modification effect is not obvious, and if it is higher than the above range, the energy consumption is high and the preparation cost is increased.
[0090] According to an embodiment of the present invention, in the step (1), during the preparation of the intermediate modified MXene / Au, the mass concentration of the substrate modified MXene is 1-5 mg mL -1 .
[0091] According to an embodiment of the present invention, in the step (1), during the preparation of gold nanoparticles, the mass concentration of the chloroauric acid solution is 1-2wt.%, the reducing agent is one or more of citric acid, hydrated citric acid, and sodium citrate, with a mass concentration of 1-2wt.%, and the reduction time is 1-4h.
[0092] The ratio of reducing agent to chloroauric acid is directly related to the reduction effect of gold nanoparticles. Since the gold in chloroauric acid is trivalent and citric acid has three reducing hydroxyl groups, the ratio of reducing agent to chloroauric acid is 1:1 or the reducing agent dosage is higher than that of chloroauric acid. If the reducing agent dosage is too low, the yield of gold nanoparticles is low and the size is large, the specific surface area is small, and the electrochemical activity is low. If the reduction time is lower than the above range, the yield of gold nanoparticles is low, and if it is higher than the above range, the cost is wasted.
[0093] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the substrate is prefabricated modified MXene / Au, and the mass concentration in the solvent acetonitrile is 0.5-2 mg mL -1 .
[0094] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the template molecule is tyrosine, and the molar concentration of tyrosine in the solvent acetonitrile is 0.01-0.02M.
[0095] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the functional monomer is one or more of acrylamide (AM), acrylic acid (AA), and 4-vinylpyridine (4VP), and the molar concentration in the solvent acetonitrile is 0.04-0.08M.
[0096] The above-mentioned organic molecules can be connected with tyrosine through hydrogen bonds, and the hydrogen bond formation energy calculated by density functional theory is negative, which can proceed spontaneously, while the other common functional monomers cannot spontaneously connect with tyrosine through hydrogen bonds at room temperature; when the reaction concentration is lower than the above range, fewer specific recognition sites are formed and the specific recognition effect is poor; when the reaction concentration is higher than the above range, not only is the cost wasted, but the polymer layer formed on the substrate-modified MXene / Au surface is thicker, which seriously reduces the electrochemical activity of the probe.
[0097] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the cross-linking agent is one or more of N,N-methylenebisacrylamide (MBA) or ethylene glycol dimethacrylate (EGDMA), and the molar concentration in the solvent acetonitrile is 0.05-0.2M.
[0098] Crosslinking agents can crosslink ordinary polymers into complex three-dimensional network structures with stable structures and wide applicability. When the concentration is lower than the above range, the strength of the three-dimensional network structure formed is low. When the concentration is higher than the above range, the three-dimensional network structure formed by the polymer is too dense and the polymer layer is thick, which seriously reduces the electrochemical activity of the probe.
[0099] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the initiator is one or more of dibenzoyl peroxide (BPO) or azobisisobutyronitrile (AIBN), and the mass concentration in the solvent acetonitrile is 0.5-1.5 mg mL -1 .
[0100] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the polymerization environment is an oxygen-free environment, the polymerization reaction temperature is 55-65° C., and the polymerization reaction time is 8-24 h.
[0101] The preparation method of MIG is free radical thermal polymerization. If oxygen is not removed during the polymerization process, oxygen will quench the free radicals and the polymerization cannot be initiated. If the polymerization temperature is lower than the above range, the initiator cannot be cracked into free radicals to initiate polymerization. If it is higher than the above range, the polymerization reaction is too violent and the resulting polymer layer is thick, which seriously reduces the electrochemical activity of the probe. If the polymerization reaction time is lower than the above range, less polymer is formed and the substrate-modified MXene / Au cannot be completely wrapped. If it is higher than the above range, the energy consumption is high and the cost is wasted.
[0102] According to an embodiment of the present invention, in the step (1), during the preparation of MIG, the eluent is one or more of methanol, ethanol, formic acid, and acetic acid, the number of elutions is 3-5 times, and the drying method is freeze-drying.
[0103] MIG will produce specific recognition cavities only after cleaning the template molecules, and the specific recognition ability is activated. Using the above-mentioned polar solvents to elute the template molecules can effectively destroy the hydrogen bonds. If the elution times are lower than the above range, all template molecules cannot be cleaned away, and the specific recognition effect of MIG is limited. If the elution times are higher than the above range, the cost is wasted.
[0104] According to an embodiment of the present invention, in step (2), the adhesive is chitosan acetic acid solution or chitosan formic acid solution, wherein the mass concentration of chitosan is 1-5 mg mL -1 The concentration of probe-modified MXene / Au / MIG in the adhesive was 1-5 mg mL -1 .
[0105] Chitosan is insoluble in water, so an organic solvent is needed to dissolve it. Acetic acid or formic acid can fully dissolve chitosan to obtain a uniform adhesive. If the adhesive concentration is lower than the above range, the bonding effect is not good, and the sensing probe may fall off during the test; if it is higher than the above range, there will be more solid residues after the adhesive dries, affecting the sensing performance of the sensor. If the probe concentration is lower than the above range, the sensor sensitivity is low; if it is higher than the above range, the probes will be stacked, and the sensitivity of the sensor cannot be effectively improved, which also wastes costs.
[0106] Compared with the prior art, the present invention has at least one of the following advantages and beneficial effects:
[0107] (1) The present invention provides a portable electrochemical sensor for specific detection of tyrosine, which has the advantages of strong specificity, high sensitivity and good stability;
[0108] (2) The probe material contains highly electrochemically active modified MXene and Au nanoparticles, which improve the detection performance of the electrochemical sensor. The probe material contains MIG with specific recognition ability on the outside, which can selectively capture tyrosine molecules for identification and detection, avoiding signal interference from other compounds with similar structures. It has good application prospects in tyrosine detection.
[0109] (3) The present invention provides a method for preparing a portable electrochemical sensor for specific detection of tyrosine, which has the characteristics of simple and fast process, strong performance, higher production capacity, and is suitable for industrial-scale production;
[0110] (4) The present invention provides a method for preparing a portable electrochemical sensor for specifically detecting tyrosine, which can identify and detect tyrosine in actual human body fluids (urine), and has inspiring significance for clinical diagnosis and treatment and home medical use. BRIEF DESCRIPTION OF THE DRAWINGS
[0111] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0112] Figure 1 The field emission scanning electron microscope (FESEM) images of the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG in Example 1, wherein (a)-(d) correspond to the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG, respectively; wherein the original MXene presents a good two-dimensional multilayer structure, the interlayer spacing of the modified MXene is larger and can load more gold nanoparticles, the Au nanoparticles in the modified MXene / Au are less than 20 nanometers, and after MIG loading, the dense polymer wraps the substrate to obtain a specific electrochemical sensing probe;
[0113] Figure 2 Transmission electron microscope (TEM) images of original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG in Example 1, wherein (a)-(d) correspond to original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG, respectively; wherein the original MXene presents a good two-dimensional multilayer structure, the modified MXene has a larger interlayer spacing and can load more gold nanoparticles, and Au nanoparticles smaller than 20 nanometers appear as black dots in TEM, and after MIG loading, the dense polymer wraps the substrate to obtain a specific electrochemical sensing probe;
[0114] Figure 3 The powder X-ray diffraction (XRD) patterns of the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG in Example 1, wherein (a)-(d) correspond to the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG, respectively; MXene has obvious crystalline characteristics, corresponding to the card JCPDS no.32-1383 of Ti3C2, in the modified MXene, the diffraction peak has a slight negative shift, the gold nanoparticles correspond to the card JCPDS no.04-0784, and MIG, as an amorphous polymer, has a typical bulge at about 20°;
[0115] Figure 4The Fourier transform infrared (FTIR) spectra of the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG in Example 1, wherein (a)-(d) correspond to the original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG, respectively; wherein 3500cm -1 The characteristic peak near is the stretching vibration of hydroxyl (-OH), 2900cm -1 The characteristic peak nearby is the stretching vibration of carbon and hydrogen (-CH), 1650cm -1 The characteristic peak near is the stretching vibration of the carbonyl group (-C=O), 1400cm -1 The characteristic peak nearby is the carbon-carbon (CC) single bond;
[0116] Figure 5 The peak spectra of each element of the X-ray photoelectron spectroscopy (XPS) of the original MXene in Example 1, where (a)-(d) correspond to the chemical states of the four elements of carbon, oxygen, fluorine, and titanium. The carbon element can be fitted into three characteristic peaks of CO, CC, and C-Ti, the oxygen element can be fitted into two characteristic peaks of O-Ti and OC, the fluorine element can be fitted into two characteristic peaks of F-Ti and FC, and the atomic content is 15.96%. The characteristic peaks of the Ti element are fitted into 2p 1 / 2 and 2p 3 / 2 and its satellite peaks;
[0117] Figure 6 The X-ray photoelectron spectroscopy (XPS) peak spectra of the modified MXene in Example 1 are as follows, where (a)-(d) correspond to the chemical states of the four elements carbon, oxygen, fluorine, and titanium. The carbon element can be fitted into three characteristic peaks of CO, CC, and C-Ti, the oxygen element can be fitted into two characteristic peaks of O-Ti and OC, and the fluorine element can be fitted into two characteristic peaks of F-Ti and FC. The atomic content is 6.50%, which proves that the modification is successful. The fluorine groups on the surface of MXene are replaced by hydroxyl groups, and the characteristic peaks of the Ti element are fitted into 2p 1 / 2 and 2p 3 / 2 and its satellite peaks;
[0118] Figure 7 The cyclic voltammetry (CV) curves of bare SPE and portable electrochemical sensor modified MXene / Au / MIG-SPE. Among them, the oxidation peak and reduction peak of SPE slightly increased and shifted after the specific sensing probe modified MXene / Au / MIG was modified, proving the successful modification of the probe;
[0119] Figure 8The electrochemical impedance spectroscopy (EIS) curves of bare SPE and portable electrochemical sensor modified MXene / Au / MIG-SPE. Among them, the charge transfer resistance of SPE slightly decreased after the specific sensing probe modified MXene / Au / MIG was modified, proving the successful modification of the probe;
[0120] Fig. 9 The CV curves of bare SPE at different bending angles. No matter when the flexible SPE is bent at 30°, 60°, or 90°, the CV curves have no obvious fluctuations, and the electrochemical signals are within the allowable error range, proving the portable application potential of flexible SPE.
[0121] Fig.10 The differential pulse voltammetry (DPV) curves of the portable electrochemical sensor modified MXene / Au / MIG-SPE for tyrosine standard solutions of different concentrations. As the concentration of tyrosine increases, the electrochemical signal of the sensor also increases accordingly;
[0122] Fig.11 The results of fitting the electrochemical test data using a suitable mathematical model. The linear detection range of tyrosine for the portable electrochemical sensor modified MXene / Au / MIG-SPE is 0.02-100μM, the minimum detection limit is 6nM, the quantitative limit is 20nM, and the sensitivity is 0.66μAμM -1 cm -2 ;
[0123] Fig.12 The specificity test results of the portable electrochemical sensor modified MXene / Au / MIG-SPE. When detecting 1μM tyrosine, the electrochemical signals of other organic compounds with similar structures were small, which had little interference with the detection of tyrosine, proving the excellent selectivity of the sensor.
[0124] Fig.13 The anti-interference test results of the portable electrochemical sensor modified MXene / Au / MIG-SPE. When detecting 1μM tyrosine, the electrochemical signal fluctuation caused by the change of other inorganic salt ion concentrations was small, which proved the excellent anti-interference of the sensor.
[0125] Fig.14 The repeatability test results of the portable electrochemical sensor modified with MXene / Au / MIG-SPE. In the five consecutive test results, the relative standard deviation of the sensor's test results was only 1.12%, proving the excellent repeatability of the sensor;
[0126] Fig.15The reproducibility test results of the portable electrochemical sensor modified with MXene / Au / MIG-SPE. After preparing 5 sensors using the same method, the same concentration of tyrosine was tested in turn. The relative standard deviation of the sensor test results was only 1.75%, proving the excellent reproducibility of the sensor.
[0127] Fig.16 The stability test results of the MXene / Au / MIG-SPE modified for portable electrochemical sensors. In the test for one month, the current signal only decreased to 95.48%, proving the excellent stability of the sensor;
[0128] Fig.17 The portable electrochemical sensor modified MXene / Au / MIG-SPE was used to specifically identify and detect tyrosine in actual human urine. The test method was the chronoamperometric (CA) method. The tyrosine content could be calculated based on the previous linear regression equation, and then the physiological level of the human body could be determined.
[0129] Fig.18 The schematic diagram of the design dimensions of SPE. Among them, the electrode with a circle in the center is the working electrode (WE), which is mainly used to load the specific electrochemical probe PDA-PB, detect vitamin C and generate electrochemical signals in the subsequent test process, the electrode with about 3 / 4 arc on the upper part is the counter electrode (CE), which can ensure the smooth flow of current in the working electrode so that the reaction under study occurs on the working electrode, and the electrode with about 1 / 4 arc on the lower part is the reference electrode (RE), which is used to control the potential difference between the electrodes;
[0130] Fig.19 Schematic diagram of the electrochemical sensing mechanism of MXene / Au / MIG-SPE modified for tyrosine and portable electrochemical sensor, including the reaction route and proton / electron transfer. DETAILED DESCRIPTION
[0131] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0132] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0133] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0134] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0135] Example 1
[0136] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0137] (1) Preparation of pristine MXene:
[0138] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0139] (2) Preparation of modified MXene:
[0140] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0141] (3) Preparation of modified MXene / Au:
[0142] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0143] (4) Preparation of modified MXene / Au / MIG:
[0144] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0145] Example 2
[0146] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0147] (1) Preparation of pristine MXene:
[0148] 2 g of Ti2AlC-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0149] (2) Preparation of modified MXene:
[0150] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0151] (3) Preparation of modified MXene / Au:
[0152] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0153] (4) Preparation of modified MXene / Au / MIG:
[0154] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0155] Example 3
[0156] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0157] (1) Preparation of pristine MXene:
[0158] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0159] (2) Preparation of modified MXene:
[0160] 0.5 g of original MXene was dispersed in 60 mL of 3 M potassium hydroxide (KOH) solution under magnetic stirring and reacted at room temperature for 24 h. The solution was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0161] (3) Preparation of modified MXene / Au:
[0162] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0163] (4) Preparation of modified MXene / Au / MIG:
[0164] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0165] Example 4
[0166] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0167] (1) Preparation of pristine MXene:
[0168] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0169] (2) Preparation of modified MXene:
[0170] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0171] (3) Preparation of modified MXene / Au:
[0172] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% hydrated sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0173] (4) Preparation of modified MXene / Au / MIG:
[0174] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0175] Example 5
[0176] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0177] (1) Preparation of pristine MXene:
[0178] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0179] (2) Preparation of modified MXene:
[0180] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0181] (3) Preparation of modified MXene / Au:
[0182] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% citric acid solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0183] (4) Preparation of modified MXene / Au / MIG:
[0184] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0185] Example 6
[0186] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0187] (1) Preparation of pristine MXene:
[0188] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0189] (2) Preparation of modified MXene:
[0190] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0191] (3) Preparation of modified MXene / Au:
[0192] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0193] (4) Preparation of modified MXene / Au / MIG:
[0194] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of ethylene glycol dimethacrylate, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0195] Example 7
[0196] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0197] (1) Preparation of pristine MXene:
[0198] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0199] (2) Preparation of modified MXene:
[0200] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0201] (3) Preparation of modified MXene / Au:
[0202] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0203] (4) Preparation of modified MXene / Au / MIG:
[0204] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of dibenzoyl peroxide were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0205] Example 8
[0206] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0207] (1) Preparation of pristine MXene:
[0208] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0209] (2) Preparation of modified MXene:
[0210] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0211] (3) Preparation of modified MXene / Au:
[0212] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0213] (4) Preparation of modified MXene / Au / MIG:
[0214] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with methanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0215] Example 9
[0216] The preparation method of a portable electrochemical sensor for specific detection of tyrosine comprises the following steps:
[0217] (1) Preparation of screen printed electrodes (SPE):
[0218] The 0.1 mm thick PET was cleaned and dried with anhydrous ethanol, and then the three-electrode substrate was printed by screen printing using graphite ink according to the pre-ordered template and completely dried; the reference electrode was printed by screen printing using silver paste ink according to the pre-ordered template and SPE was obtained after completely drying.
[0219] (2) Preparation of MXene / Au / MIG-SPE modified for portable electrochemical sensors:
[0220] 0.02 g of chitosan was dissolved in 2 mL of 2 M acetic acid solution as an adhesive, and 5 mg of prefabricated probe-modified MXene / Au / MIG-SPE was dispersed in the above solution to obtain a probe modification solution; 5 μL of the probe modification solution was added dropwise to the working electrode surface of the SPE, and after drying at room temperature, a portable electrochemical sensor modified MXene / Au / MIG-SPE was obtained.
[0221] Example 10
[0222] The preparation method of a portable electrochemical sensor for specific detection of tyrosine comprises the following steps:
[0223] (1) Preparation of screen printed electrodes (SPE):
[0224] The 0.1 mm thick PET was cleaned and dried with anhydrous ethanol, and then the three-electrode substrate was printed by screen printing using graphite ink according to the pre-ordered template and completely dried; the reference electrode was printed by screen printing using silver paste ink according to the pre-ordered template and SPE was obtained after completely drying.
[0225] (2) Preparation of MXene / Au / MIG-SPE modified for portable electrochemical sensors:
[0226] 0.02 g of chitosan was dissolved in 2 mL of 2 M formic acid solution as an adhesive, and 5 mg of prefabricated probe-modified MXene / Au / MIG-SPE was dispersed in the above solution to obtain a probe modification solution; 5 μL of the probe modification solution was added dropwise to the working electrode surface of the SPE, and after drying at room temperature, a portable electrochemical sensor modified MXene / Au / MIG-SPE was obtained.
[0227] Embodiment 11
[0228] The preparation method of a portable electrochemical sensor for specific detection of tyrosine comprises the following steps:
[0229] (1) Preparation of screen printed electrodes (SPE):
[0230] The 0.1 mm thick PET was cleaned and dried with anhydrous ethanol, and then the three-electrode substrate was printed by screen printing using graphite ink according to the pre-ordered template and completely dried; the reference electrode was printed by screen printing using silver paste ink according to the pre-ordered template and SPE was obtained after completely drying.
[0231] (2) Preparation of MXene / Au / MIG-SPE modified for portable electrochemical sensors:
[0232] 0.02 g of chitosan was dissolved in 2 mL of 2 M acetic acid solution as an adhesive, and 10 mg of prefabricated probe-modified MXene / Au / MIG-SPE was dispersed in the above solution to obtain a probe modification solution; 5 μL of the probe modification solution was added dropwise to the working electrode surface of the SPE, and after drying at room temperature, a portable electrochemical sensor modified MXene / Au / MIG-SPE was obtained.
[0233] Test Example 1
[0234] This test example uses the DPV method in the electrochemical method as the test means to study the specific electrochemical detection effect of tyrosine on the portable electrochemical sensor modified MXene / Au / MIG-SPE assembled at the specific electrochemical sensing probe level prepared in Example 1 and Example 9. First, the electrochemical DPV detection scheme of tyrosine standard solutions of different concentrations (100μM, 50μM, 20μM, 10μM, 5μM, 2μM, 1μM, 0.5μM, 0.2μM, 0.1μM, 0.05μM, 0.02μM) was established and tested at room temperature and pressure. Among them, the total volume of the experimental solution was maintained at 50mL, the electrolyte was universal phosphate buffer (PBS), the concentration was 0.01M, and the pH value was 7.0. After 200μL of the test solution was added to the three-electrode sensing part of the portable electrochemical sensor PDA-PB-SPE, the scanning range was 0.2-1.0V, and data was recorded every 20mV. The current density value was recorded, and the linear regression model was used to fit and calculate the linear detection range, minimum detection limit, minimum quantification limit and detection sensitivity of the prefabricated electrochemical sensor for tyrosine.
[0235] Fig.10 The middle curve represents the current density diagram after the modified MXene / Au / MIG-SPE reacts with different concentrations of tyrosine through DPV. The tyrosine concentrations represented by the curve from top to bottom are: 100μM, 50μM, 20μM, 10μM, 5μM, 2μM, 1μM, 0.5μM, 0.2μM, 0.1μM, 0.05μM, 0.02μM, and the oxidation potential is 0.608V. Fig.11 In (a), the horizontal axis is the tyrosine concentration, and the vertical axis is the current density. The linear regression model is used to fit the tyrosine concentration and the current density, and the high linear detection range of the modified MXene / Au / MIG-SPE for tyrosine is 1-100 μM, and the linear correlation coefficient is 0.9894; Fig.11 The horizontal axis in (b) is the tyrosine concentration, and the vertical axis is the current density. The linear regression model is used to fit the tyrosine concentration and current density, and the low linear detection range of the modified MXene / Au / MIG-SPE for tyrosine is 0.02-1μM, and the linear correlation coefficient is 0.9893. It can be calculated that the linear detection range of the prefabricated electrochemical sensor modified MXene / Au / MIG-SPE for tyrosine is 0.02-100μM, the minimum detection limit is 6nM, the quantitative limit is 20nM, and the sensitivity is 0.66μAμM -1 cm -2 .
[0236] Test Example 2
[0237] This test example uses the CA method in the electrochemical method as the test means to study the specific electrochemical detection effect of the portable electrochemical sensor modified MXene / Au / MIG-SPE after the specific electrochemical sensing probe level assembly prepared in Example 1 and Example 9 on tyrosine in human urine. First, the electrochemical CA detection scheme for tyrosine standard solutions in different human urine at room temperature and pressure was established and tested. Human urine was diluted 1 times with PBS with a concentration of 0.01M and a pH of 7.0, and then 200μL of the test solution was added to the three-electrode sensing part of the portable electrochemical sensor modified MXene / Au / MIG-SPE. The polarization (oxidation) potential was 0.608V, the test time was 120s, and the current density value was recorded. The tyrosine concentration in human urine was calculated by combining the linear regression equation in Test Example 1.
[0238] Fig.17 These are the electrochemical test results of human urine samples on modified MXene / Au / MIG-SPE. After calculation, the tyrosine concentrations of volunteers 1 to 8 were 81.8μM, 48.9μM, 60.6μM, 71.4μM, 51.8μM, 71.0μM, 56.2μM, and 14.6μM, respectively, which shows actual detection capabilities.
[0239] Comparative Example 1
[0240] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0241] (1) Preparation of pristine MXene:
[0242] Under magnetic stirring, 2 g of lithium fluoride was dissolved in 40 mL of 9 M hydrochloric acid, and 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%). The mixture was etched at 40 °C for 40 h, and the impurities were removed repeatedly with deionized water to make the supernatant neutral. After centrifugation, it was freeze-dried to obtain the original MXene.
[0243] (2) Preparation of modified MXene:
[0244] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0245] (3) Preparation of modified MXene / Au:
[0246] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0247] (4) Preparation of modified MXene / Au / MIG:
[0248] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0249] This comparative example studies the etching effect of the MAX phase under different acidic reaction systems. The MXene obtained by etching with the lithium fluoride / hydrochloric acid system is mostly a single-layer structure with fewer layers. The Au nanoparticles that can be loaded are less than those in Example 1, and the active sites of the MIG covered subsequently are also fewer, and the specific detection effect is poor.
[0250] Comparative Example 2
[0251] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0252] (1) Preparation of pristine MXene:
[0253] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0254] (2) Preparation of modified MXene:
[0255] 0.5 g of original MXene was dispersed in 60 mL of 1 M p-phenylenediamine solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0256] (3) Preparation of modified MXene / Au:
[0257] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0258] (4) Preparation of modified MXene / Au / MIG:
[0259] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of 4-vinylpyridine, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0260] This comparative example studies the modification effect of the original MXene under different alkaline reaction systems. The layer expansion effect of the MXene modified by the organic base system, i.e., p-phenylenediamine solution, is relatively general, the amount of Au nanoparticles that can be loaded is less than that in Example 1, and the electrochemical performance is poor.
[0261] Comparative Example 3
[0262] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0263] (1) Preparation of pristine MXene:
[0264] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0265] (2) Preparation of modified MXene:
[0266] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0267] (3) Preparation of modified MXene / Au:
[0268] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0269] (4) Preparation of modified MXene / Au / MIG:
[0270] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of acrylamide, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0271] This comparative example studies the detection effect of different functional monomers used to synthesize MIG on tyrosine. According to the DFT simulation calculation results, the hydrogen bond Gibbs free energy of 4-vinylpyridine as a functional monomer combined with tyrosine is -3.01 kcal mol -1 , the prepolymer is easier to form, and the hydrogen bond Gibbs free energy of acrylamide as a functional monomer combined with tyrosine is -1.65 kcal mol -1 , the prepolymer is more difficult to form than the above, and the specific recognition effect is poor.
[0272] Comparative Example 4
[0273] The preparation method of a specific electrochemical sensing probe for specific detection of tyrosine comprises the following steps:
[0274] (1) Preparation of pristine MXene:
[0275] 2 g of Ti3AlC2-type MAX phase was dispersed in 40 mL of hydrofluoric acid solution (40%) under magnetic stirring, etched at 40 °C for 40 h, repeatedly washed with deionized water to remove impurities and make the supernatant neutral, and freeze-dried after centrifugation to obtain the original MXene.
[0276] (2) Preparation of modified MXene:
[0277] 0.5 g of original MXene was dispersed in 60 mL of 3 M sodium hydroxide (NaOH) solution under magnetic stirring and reacted at room temperature for 24 h. The mixture was repeatedly washed with deionized water to remove impurities and make the supernatant neutral. The modified MXene was obtained by freeze-drying after centrifugation.
[0278] (3) Preparation of modified MXene / Au:
[0279] Under magnetic stirring, 50 mg of modified MXene was dispersed in 50 mL of deionized water, 2 mL of 1 wt.% chloroauric acid solution was added, and then 2 mL of 1 wt.% sodium citrate solution was added. The mixture was reacted at room temperature for 2 h, and impurities were removed by repeated washing with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au.
[0280] (4) Preparation of modified MXene / Au / MIG:
[0281] Under magnetic stirring, 50 mg of modified MXene / Au was dispersed in 50 mL of acetonitrile, and 1 mmol of template molecule tyrosine, 4 mmol of acrylic acid, 10 mmol of N,N-methylenebisacrylamide, and 20 mg of azobisisobutyronitrile were added. Nitrogen was introduced to remove oxygen. The mixture was reacted at 65 °C for 12 h. The polymer was rinsed three times with ethanol / acetic acid (9:1, V:V), and the residual organic solvent was washed away with deionized water. The mixture was centrifuged and freeze-dried to obtain modified MXene / Au / MIG.
[0282] This comparative example studies the detection effect of different functional monomers used to synthesize MIG on tyrosine. According to the DFT simulation calculation results, the hydrogen bond Gibbs free energy of 4-vinylpyridine as a functional monomer combined with tyrosine is -3.01 kcal mol -1 , the prepolymer is easier to form, and the hydrogen bond Gibbs free energy of acrylic acid as a functional monomer combined with tyrosine is -2.25 kcalmol -1 , the prepolymer is more difficult to form than the above, and the specific recognition effect is poor.
[0283] Comparative Example 5
[0284] The preparation method of a portable electrochemical sensor for detecting vitamin C comprises the following steps:
[0285] (1) Preparation of screen printed electrodes (SPE):
[0286] The 0.1 mm thick PET was cleaned with anhydrous ethanol and dried, and then the three-electrode substrate was printed by screen printing using graphite ink according to the pre-ordered template and dried; the reference electrode was printed by screen printing using silver paste ink according to the pre-ordered template and dried to obtain SPE.
[0287] (2) Preparation of MXene / Au / MIG-SPE modified for portable electrochemical sensors:
[0288] 1 mL of anhydrous ethanol was mixed with 1 mL of 5 wt.% perfluorosulfonic acid resin (Nafion) as an adhesive, and 5 mg of prefabricated probe-modified MXene / Au / MIG-SPE was dispersed in the above solution to obtain a probe modification solution; 5 μL of the probe modification solution was added dropwise to the working electrode surface of the SPE, and dried at room temperature to obtain a portable electrochemical sensor modified MXene / Au / MIG-SPE.
[0289] This comparative example studies the effects of different adhesives on the modification of biomass electrochemical sensing probes with SPE. Although perfluorosulfonic acid resin (Nafion) can also fix the probe on the surface of the working electrode, and Nafion, as a conductive polymer, will not have a significant effect on the performance of the electrochemical sensor, the toxicity of Nafion still restricts its detection in real human samples and is not suitable for home medical treatment.
[0290] In summary, the inventors evaluated the feasibility of modified MXene / Au / MIG as a specific electrochemical sensing probe, and further evaluated the feasibility, safety and stability of modified MXene / Au / MIG as a tyrosine-specific electrochemical sensing probe, and studied the preparation methods of original MXene, modified MXene, modified MXene / Au and modified MXene / Au / MIG, and evaluated the advantages and disadvantages of different preparation schemes. Subsequently, the inventors evaluated the feasibility and safety of different adhesives for modified MXene / Au / MIG modified SPE, prepared a portable electrochemical sensor modified MXene / Au / MIG for specific recognition and detection of tyrosine, and verified the detection performance, stability and portability of the sensor. Fig.18 The design dimensions of the SPE are shown. Its thickness is negligible at 0.1 mm, and the usable area is less than 6 cm 2 , the sample volume required in the actual sensing area is 200μL, which is very convenient. Subsequently, the inventors verified the feasibility of the portable electrochemical sensor modified MXene / Au / MIG in the specific recognition and detection of tyrosine in real human urine samples. This specific electrochemical sensing probe has a special specific recognition ability, strong anti-interference ability, stable and powerful performance, low process cost, and is simple and convenient. Subsequently, the sensing probe was fixed on the flexible SPE through the biomass adhesive chitosan. The method is simple and has high repeatability. After complete drying, a portable electrochemical sensor modified MXene / Au / MIG-SPE for specific detection of tyrosine was obtained.
[0291] Compared with the commercial medical enzymatic method for detecting tyrosine content, the electrochemical sensor method for detecting vitamins has greatly improved portability and also has the special specific recognition function of biological enzymes. In addition, the probe is more applicable, is not afraid of acid or alkali, and has controllable costs. Fig.19The mechanism diagram of the electrochemical reaction between the prefabricated sensor modified MXene / Au / MIG-SPE and tyrosine is shown. The current density of the entire detection process changes linearly, the detection volume is 200μL, the detection time is within 120s, the sampling volume is small, and it is convenient and efficient. Compared with other electrochemical tyrosine sensors, the sensing probe of this portable sensor has a unique specific recognition function and strong anti-interference. At the same time, in the present invention, the SPE based on the flexible PET substrate greatly enhances the practicality of the sensor. The successful recognition and detection of tyrosine in actual human urine proves the potential for clinical and home applications, and realizes portable and efficient selection and detection of tyrosine in the solution.
[0292] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
[0293] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0294] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A portable electrochemical sensor for specific detection of tyrosine, characterized in that: include: A flexible screen-printed electrode, wherein the substrate of the flexible screen-printed electrode is a polyethylene terephthalate film, and the flexible screen-printed electrode is printed with graphite ink and silver paste ink; An electrochemical sensing probe is located on the surface of the flexible screen-printed electrode, and is composed of a ternary composite material, which includes two-dimensional layered carbon / nitride, gold nanoparticles and molecular imprinting gel.
2. The portable electrochemical sensor for specific detection of tyrosine according to claim 1, characterized in that: The two-dimensional layered carbon / nitride and the gold nanoparticles are connected together through electrostatic interaction.
3. A method for preparing a portable electrochemical sensor for specific detection of tyrosine, characterized in that: include: S1: dispersing the MAX phase in an acidic solution, and removing the aluminum layer in the MAX phase through a first etching treatment to obtain an original two-dimensional layered carbon / nitride, wherein the MAX phase is a non-van der Waals layered compound; S2: dispersing the original two-dimensional layered carbon / nitride in an alkaline solution, and subjecting the original two-dimensional layered carbon / nitride to a second etching treatment to obtain a modified two-dimensional layered carbon / nitride; S3: dispersing the modified two-dimensional layered carbon / nitride in a chloroauric acid solution and mixing with a reducing agent to obtain a modified two-dimensional layered carbon / nitride / gold; S4: dispersing the modified two-dimensional layered carbon / nitride / gold in acetonitrile, and polymerizing with a template molecule, a functional monomer, a cross-linking agent, and an initiator to obtain a molecularly imprinted gel; S5: washing, centrifuging and drying the molecularly imprinted gel to obtain a specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecularly imprinted gel; S6: The specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is fixed to the surface of a flexible screen-printed electrode to obtain a portable electrochemical sensor for specific detection of tyrosine.
4. The method according to claim 3, characterized in that: The chemical composition of the MAX phase is one or two of Ti3AlC2 and Ti2AlC; Optionally, the mass concentration of the MAX phase in the first etching treatment is 0.04-0.06 g mL -1 ; Optionally, the acidic solution is one or more of a hydrofluoric acid aqueous solution, hydrochloric acid or a lithium fluoride mixed solution; Optionally, the mass fraction of the acidic solution in the first etching treatment is 30%-50%; Optionally, the temperature of the first etching treatment is 30-50°C; Optionally, the first etching treatment takes 24-48 hours.
5. The method according to claim 3, characterized in that: The solute of the alkaline solution is one or more of potassium hydroxide, sodium hydroxide and p-phenylenediamine; Optionally, the molar concentration of the alkaline solution in the second etching treatment is 1-3M; Optionally, the reaction time of the second etching treatment is 12-24 hours.
6. The method according to claim 3, characterized in that The mass concentration of the modified two-dimensional layered carbon / nitride in the mixing process is 1-5 mg mL -1 ; Optionally, the mass concentration of the chloroauric acid solution in the mixing process is 1-2wt.%; Optionally, the reducing agent is one or more of citric acid, hydrated citric acid or sodium citrate; Optionally, the mass concentration of the reducing agent in the mixing process is 1-2wt.%; Optionally, the mixing treatment time is 1-4 hours.
7. The method according to claim 3, characterized in that The mass concentration of acetonitrile is 0.5-2 mg mL -1 ; Optionally, the template molecule is tyrosine; Optionally, the molar concentration of the template molecule in acetonitrile is 0.01-0.02M; Optionally, the functional monomer is one or more of acrylamide, acrylic acid or 4-vinylpyridine; Optionally, the molar concentration of the functional monomer in acetonitrile is 0.04-0.08M; Optionally, the cross-linking agent is one or both of N,N-methylenebisacrylamide or ethylene glycol dimethacrylate; Optionally, the molar concentration of the cross-linking agent in acetonitrile is 0.05-0.2M; Optionally, the initiator is one or both of dibenzoyl peroxide and azobisisobutyronitrile; Optionally, the mass concentration of the initiator in acetonitrile is 0.2-1 mg mL -1 ; Optionally, the polymerization reaction is carried out in an oxygen-free environment; Optionally, the polymerization temperature is 55-65°C; Optionally, the polymerization reaction time is 8-24h; Optionally, the molar ratio of the template molecule, the functional monomer, and the cross-linking agent is 1:4:
10.
8. The method according to claim 3, characterized in that The eluent in the washing treatment is one or more of methanol, ethanol, formic acid or acetic acid; Optionally, the number of elutions in the washing treatment is 3-5 times; Optionally, the drying process is performed by freeze drying.
9. The method according to claim 3, characterized in that: The specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is fixed to the surface of the flexible screen-printed electrode in the following manner: A1: Grind the biomass chitosan finely and then dissolve it in an organic acid solution to obtain a sensing probe adhesive; A2: Use graphite ink and silver paste ink to print flexible screen-printed electrodes according to the pre-made screen, and dry completely; A3: The specific electrochemical sensing probe modified two-dimensional layered carbon / nitride / gold / molecular imprinting gel is dispersed in the adhesive to obtain a uniform suspension, the suspension is pipetted and dripped onto the working electrode surface of the flexible screen-printed electrode, and after drying, a portable electrochemical sensor for specific detection of tyrosine is obtained.
10. The method according to claim 9, characterized in that The adhesive is chitosan acetic acid solution or chitosan formic acid solution; Optionally, the mass concentration of the adhesive is 1-5 mg mL -1 ; Optionally, the concentration of the modified two-dimensional layered carbon / nitride / gold / molecularly imprinted gel in the adhesive is 1-5 mg mL -1 ; Optionally, the amount of the suspension is 5-10 μL; Optionally, the drying environment is a vacuum environment; Optionally, the drying temperature is 30-40°C.